Efficacy and safety of nilotinib in patients with kit-mutated metastatic or inoperable melanoma: Final results from the global, single-arm, phase ii team trial - Guo, J.; Carvajal, R. D.; Dummer, R.; Hauschild, A.; Daud, Adil; Bastian, B. C.; Markovic, S. N.; Queirolo, P.; Arance, Ana; Berking, C.; Camargo, V.; Herchenhorn, D.; et al. (Annals of Oncology, 2017)
Background: The single-arm, phase II Tasigna Efficacy in Advanced Melanoma (TEAM) trial evaluated the KIT-selective tyrosine kinase inhibitor nilotinib in patients with KIT-mutated advanced melanoma without prior KIT inhibitor treatment. Patients and methods: Forty-two patients with KIT-mutated advanced melanoma were enrolled and treated with nilotinib 400mg twice daily. TEAM originally included a comparator arm of dacarbazine (DTIC)-treated patients; the design was amended to a single-arm trial due to an observed low number of KIT-mutated melanomas. Thirteen patients were randomized to DTIC before the protocol amendment removing this study arm. The primary endpoint was objective response rate (ORR), determined according to Response Evaluation Criteria In Solid Tumors. Results: ORR was 26.2% (n1/411/42; 95% CI, 13.9%-42.0%), sufficient to reject the null hypothesis (ORR ≤10%). All observed responses were partial responses (PRs; median response duration, 7.1 months). Twenty patients (47.6%) had stable disease and 10 (23.8%) had progressive disease; 1 (2.4%) response was unknown. Ten of the 11 responding patients had exon 11 mutations, four with an L576P mutation. The median progression-free survival and overall survival were 4.2 and 18.0 months, respectively. Three of the 13 patients on DTIC achieved a PR, and another patient had a PR following switch to nilotinib. Conclusion: Nilotinib activity in patients with advanced KIT-mutated melanoma was similar to historical data from imatinibtreated patients. DTIC treatment showed potential activity, although the low patient number limits interpretation. Similar to previously reported results with imatinib, nilotinib showed greater activity among patients with an exon 11 mutation, including L576P, suggesting that nilotinib may be an effective treatment option for patients with specific KIT mutations. Clinical Trial Registration: ClinicalTrials.gov, NCT01028222.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Dacarbazine; Imatinib; KIT; Melanoma; Nilotinib; Tyrosine kinase inhibitor